Development of E-book “FLASHBACK SEJARAH SASTRA” as a Supporting Source of Literaturgeschichte Course of German Literature Universitas Negeri Malang - Ade Putri Maysari; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This research and development aim to test the validity of the feasibility of the e-book "Flashback Sejarah Sastra" so that it can be used as a source of supporting learning in the Literaturgeschichte course. The research and development model used is the ADDIE development model. The ADDIE development model is divided into five stages, namely: 1) analyze, 2) design, 3) develop, 4) implement, and 5) evaluate. The results obtained from this research and development are that students who have taken the Literaturgeschichte course find the e-book “Flashback Sejarah Sastra" interesting and can support learning.